2014
DOI: 10.1016/j.micinf.2013.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli K1 induces pterin production for enhanced expression of Fcγ receptor I to invade RAW 264.7 macrophages

Abstract: Macrophages serve as permissive niches for Escherichia coli (E. coli) K1 to attain high grade bacteremia in the pathogenesis of meningitis in neonates. Although pterin levels are a diagnostic marker for immune activation, the role of macrophages in pterin production and in the establishment of meningitis is unknown. Here, we demonstrate that macrophages infected with E. coli K1 produce both neopterin and biopterin through increased expression of GTP-cyclohydrolase 1 (GCH1). Of note, increased production of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The expression of OmpA is critical for survival inside PMNs after phagocytosis as OmpA − E. coli failed to survive. The phagocytosis of OmpA − E. coli by PMNs produces an enormous amount of reactive oxygen species (ROS) [ 122 ]. In contrast, OmpA + E. coli suppressed the release of ROS even in the presence of external stimuli such as LPS, indicating that E. coli overrides PMN machinery to prevent antimicrobial activity.…”
Section: Escherichia Coli K1-induced Neonatal Meningitismentioning
confidence: 99%
“…The expression of OmpA is critical for survival inside PMNs after phagocytosis as OmpA − E. coli failed to survive. The phagocytosis of OmpA − E. coli by PMNs produces an enormous amount of reactive oxygen species (ROS) [ 122 ]. In contrast, OmpA + E. coli suppressed the release of ROS even in the presence of external stimuli such as LPS, indicating that E. coli overrides PMN machinery to prevent antimicrobial activity.…”
Section: Escherichia Coli K1-induced Neonatal Meningitismentioning
confidence: 99%
“… 128 Polybacterial infection inhibited the level BH4 in the mesenteric artery and colon, worsening atherosclerotic vascular disease. 130 However, Escherichia coli K1 increased GCH1 131 or BH4 132 expression in human brain microvascular endothelial cells and macrophage to evade surveillance by the immune system.…”
Section: Intestinal Microorganisms Act On Ferroptosismentioning
confidence: 98%
“…Leib and colleagues have found that ROS was produced from predominantly polymorphonuclear leukocytes in the subarachnoid and ventricular space, cortical vessels, endothelial cells in group B streptococci meningitis [ 128 , 129 ]. There is also a large generation of ROS from microglia, neurons, and astrocytes induced by E. coli lipopolysaccharides, cytokines (TNF-α and interleukin-1β [IL-1] β) [ 130 , 131 , 132 , 133 ]. Oxidative stress or free radicals increasingly became a vital event in promoting the development of neuronal injury during bacterial meningitis.…”
Section: Neuroprotective Properties Of Melatonin Against Bacterialmentioning
confidence: 99%